Instability in Dryland Agriculture-a Study of a Drought-Prone District in Karnataka - Gajananda, T M; Sharma, B M (Annals of Arid Zone, 2016)
Realising that an understanding of the pattern of instability in farming in dry land areas becomes all the more important in formulating policies for the development of such areas which produce the bulk of foodgrains, pulses and oilseeds, an attempt was made in this study to examine the nature and extent of instability in farming in one of the drought-prone districts namely. Tumkur of Karnataka. Instability was examined with the help of coefficient of varia tion around the trend (CVt) of crop and livestock yields. prices and returns. Probability of failure and distribution of crop yields were also attempted. The results indicated that instability was very high in crop farming as compared to livestock rearing. Further, yield variability was found to be higher than price variability. Below average yields of one crop were accompanied by other crops in 3-4 years. Prices were found to be moving in the same direction. It is suggested to follow livestock rearing and sericulture on the farms. Besides, adoption of dry farming practices and re-introduction of crop insurance in the area were suggested for the development of the district.